STRATEGI PENGEMBANGAN UMKM DI KOTA DUMAI DALAM MENGHADAPI PERSAINGAN PASAR DIGITAL - Lastri, Novelma; Hartutik, Dwi; Aditiya, Variza; Mustafa, Said; Musdiana, Andi Desy (Smart Education, 2025)
Abstract: This study examines the development strategies of Micro, Small and Medium Enterprises and the challenges faced in Dumai City in facing digital market competition. Local governments play an essential role in supporting MSMEs through financial support, training, mentoring, and facilitation of market access and technology, including the promotion of local products through digital media. Online marketing, including the utilization of social media, marketplaces, and websites, has been shown to improve the competitiveness of MSMEs by expanding market reach, increasing consumer interaction, and driving sales. Digital transformation, as the integration of digital technology in all aspects of business, is imperative for MSMEs to change the way they operate and deliver value to customers, as well as expand market reach. Nonetheless, the development of MSMEs in Dumai City still faces various obstacles, including limited access to capital and technology, difficulties in optimizing online marketing features, as well as digital era challenges such as limited resources, lack of technological understanding, fierce competition, and low digital literacy and infrastructure. Therefore, a comprehensive strategy is needed to empower MSMEs to compete effectively in the digital market. Keywords: MSMEs, Development, Digital Marketing, Digital Transformation, Challenges. Abstrak: Penelitian ini mengkaji strategi pengembangan Usaha Mikro, Kecil, dan Menengah serta tantangan yang dihadapi di Kota Dumai dalam menghadapi persaingan pasar digital. Pemerintah daerah memegang peranan esensial dalam mendukung UMKM melalui dukungan finansial, pelatihan, pendampingan, serta fasilitasi akses pasar dan teknologi, termasuk promosi produk lokal melalui media digital. Pemasaran online, mencakup pemanfaatan media sosial, marketplace, dan website, terbukti meningkatkan daya saing UMKM dengan memperluas jangkauan pasar, meningkatkan interaksi konsumen, dan mendorong penjualan. Transformasi digital, sebagai integrasi teknologi digital dalam semua aspek bisnis, merupakan keharusan bagi UMKM untuk mengubah cara beroperasi dan memberikan nilai kepada pelanggan, serta memperluas jangkauan pasar. Meskipun demikian, pengembangan UMKM di Kota Dumai masih menghadapi berbagai hambatan, meliputi keterbatasan akses terhadap modal dan teknologi, kesulitan dalam mengoptimalkan fitur pemasaran online, serta tantangan era digital seperti keterbatasan sumber daya, kurangnya pemahaman teknologi, persaingan ketat, dan rendahnya literasi serta infrastruktur digital. Oleh karena itu, diperlukan strategi komprehensif untuk memberdayakan UMKM agar mampu bersaing efektif di pasar digital. Kata kunci: UMKM, Pengembangan, Pemasaran Digital, Transformasi Digital, Tantangan.